Crucial Maps In The Early Cartography And Place-Nomenclature Of The Atlantic Coast of Canada - Ganong, William F. (Special publications (Royal Society of Canada) ;, 1964)
Crucial Mapswas the last series of articles by the author, the results of his systematic investigations into New Brunswick's physiography, aborigines, early explorations, wars and settlements.